Maternal knowledge and practices about complementary feeding in children from zero to two years of age (Research, Society and Development, 2022)
This study aimed to know the maternal practices on complementary feeding in children from zero to two years old. This is a descriptive study of qualitative approach, developed in a primary health care unit (UAPS) in the city of Fortaleza, Brazil. The chosen unit is part of the area of coverage and health responsibility of the Universidade Estadual do Ceará (UECE), and practice field of students of the nursing course of that university. The research followed the quality improvement studies framework COREQ of EQUATOR network. Initially, 20 mothers participated in the study, chosen by convenience, with a final sample of 19 mothers. Data collection took place in September 2018 through a semi-structured interview. The responses were recorded, with an average duration of ten minutes. The information was transcribed to organize the textual corpus, analyzed and processed by IRAMUTEQ software. The textual corpus was composed of 88 segments, of which 68 elementary context units were obtained, producing six classes: food offered, guidance, knowledge of mothers, mothers' facilities, mothers' difficulties, maternal feelings. The study showed that mothers are aware of the food introduction in children under 2 years, however the onset of these complementary foods are difficult, because there are feelings of fear and doubt, especially anxiety and insecurity related to adaptation to the new food. The study showed that mothers are aware of the food introduction in children under 2 years, however the beginning of these complementary foods are difficult, because feelings of fear and doubt arise, especially anxiety and insecurity related to the child's adaptation to new food discoveries, based on these desires, in this new phase of the child's life, it is necessary that professionals offer a support network of guidance and clarification to mothers and/or those responsible for the child